Sulfide interlayered cobalt-based oxynitrides for efficient oxygen evolution reaction in neutral pH water and seawater - Ahmed Badreldin (9574341) (2023)
Sluggish kinetics of the anodic oxygen evolution reaction (OER) and minor upstream upsets in feed water quality remain bottlenecks for efficient water electrolysis, which is exacerbated under near-neutral pH environments due to H2O dissociation. In this work, we report the introduction of a NiSx interlayer in a Co-(NiFe) oxide/nitride catalyst on nickel foam substrate. Postmortem OER characterization in neutral pH synthetic seawater (SSW) shows that stable cationic [Co-(NiFe)]δ+ and anionic [O-N]δ– surface species coupled with the NiSx interlayer accelerate H2O dissociation, thereby enhancing activity and kinetics. The electrocatalysts exhibit stable performance at 100 mA cm−2 for 50 h in alkaline and neutral pH SSW with 350 and 425 mV of overpotential, respectively. The faradaic efficiency of the NiSx interlayer catalysts is enhanced by 10.3% and 8.5% achieving 94.5% and 87.4% under alkaline and neutral pH SSW, respectively, during chronoamperometry tests at a high applied voltage of 1.75 V (vs. RHE). Other Information Published in: Applied Catalysis B: Environmental License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apcatb.2023.122599 Additional institutions affiliated with: Chemical Engineering Program - TAMUQ